The Politics of Objects: Eliza Cook’s Biographies of Things - Fabienne Moine (Cahiers Victoriens et Edouardiens)
Eliza Cook’s poetry of daily life is intertwined with her Chartist engagement. While her poems often denounce the forces of oppression that threaten social peace and the daily life of simple people, her biographies or fictitious autobiographies of things about duly called ‘feminine’ artefacts support her protofeminist engagement while challenging the limits of the domestic sphere. The ‘voice’ of things is used to denounce social and economic inequalities. The first part of this study concentrates on Cook’s denunciation of the accumulation of manufactured objects in bourgeois homes while, in her own interiors, objects and rooms encourage the return to more community-centred values. Then this article turns to the social lives of things, more precisely of raw material, whose dignity is restored by giving them a voice and by showing that their self-sacrifice ensures the preservation of the community’s identity and promotes social cohesion. Finally, Cook’s biographies of things challenge the economic models that value profit, property and individualism as she presents new forms of exchange and enhances the possibility of a counter-model of consumption that secures fairer social and economic patterns.